Effect of Pregabalin on Succinylcholine Induced Fasciculation, Myalgia and Hyperkalemia in Spine Surgery - Iqbal, Mohammad Jahid; Mahabuzzaman, Mohammad; Hossain, Gisan; Kabir, Mohammod Humayan; Haider, Md Ali; Bhowmick, Lipon Kanti (Community Based Medical Journal, 2023)
A randomized control trial was done between January and December of 2018, in the Department of Anaesthesia, Analgesia, Palliative & Intensive Care Medicine of Dhaka Medical College Hospital, Bangladesh, to evaluate the preventive effect of pregabalin on succinylcholine induced adverse effects, i.e., fasciculation, myalgia and hyperkaliemia in spine surgery. Sixty patients of elective spine surgery under general anaesthesia were selected and divided into two groups. Pregabalin 150 mg was given to one group and matching placebo was given to another group orally with sips of water one hour before surgery. Succinylcholine 1.5 mg/kg was given after induction agent. Muscle fasciculation was observed just after succinylcholine administration. Serum potassium was measured 5 minutes before induction and 5 minutes after succinylcholine administration. After completion of surgery reversal was given. Time of first analgesic demand was recorded. Injection Morphine 0.15 mg/kg intramuscular was given when patient complained about pain. Myalgia (muscle pain not associated with surgery) was observed 24 hours after anaesthesia and total morphine consumption was recorded. Use of pregabalin 150 mg one hour before surgery reduced the severity of fasciculation and the incidence and severity of postoperative myalgia. It also reduced the rise of serum potassium concentration after succinylcholine administration though the rise was within normal limit. Pregabalin also reduced the total opioid consumption after surgery. CBMJ 2023 January: Vol. 12 No. 01 P: 73-80